Future Anxiety among university students in light of gender and speciality variables: Field study at some colleges of Jijel University - Allouti, Souhila (Journal of Human Sciences, 2022)
This study aimed to identify the level of Future Anxiety among first-year master’s students at some colleges of Jijel University, and to identify their differences in this variable by gender variable (males and females) and Study Speciality, using the descriptive method. The study was based on a sample of (304) students, applied to the future anxiety scale of "Ghaleb Mohammed Ali Al-Mashikhy", and used the (T) test to calculate the importance of differences. The results showed that the level of Future anxiety among master’s students at Jijel University was low, and there were statistically significant differences at the level (0.01) between them in this variable by gender, while these differences did not appear by speciality.